Aflatoxin and Sclerotia Production in Clinical Isolates of Aspergillus Flavus Group - P Kordbacheh; A Jebali; M Mahmoudi; F Zaini; P Dehghan; S Rezaei (Tehran University of Medical Sciences, 2008)
Backgrounds: To obtain information about clinical isolates of Aspergillus flavus group. Methods: We examined 55 isolates [45 clinical, 10 reference (6 from culture collections, 4 local reference)] for toxicology, growth rates, and morphological and physiological characteristics. Modified Czapek Agar (CZ) and Malt Extract Agar (MEA) were used for observing microscopic morphology and measuring fungal structures. Two additional media, Potato Dextrose Agar (PDA) and a modified Rice Agar (RA), were used to detect fluorescence under UV light. The presence of aflatoxin in culture extracts was confirmed by thin-layer chromatography (TLC). Results: 66.6% and 55.5% of clinical samples showed different shade of fluorescence on RA and PDA, respectively, after exposure to UV light. Fifteen (33.3%) of the clinical isolates and 3 (30%) of the reference strains produced sclerotia on Czapek Yeast Agar (CYA) at 37° C. Sclerotia formation was promoted at 37°C in comparison with 28°C on CYA medium (P< 0.001). Five (11.11%) of the clinical isolates, the Iranian A. flavus soil reference strain and A. parasiticus ATCC15517 were confirmed to be aflatoxiginc by TLC. From two clinical toxigenic isolates (of 5) which were fluorescence positive on PDA, only one produced fluorescence on RA after exposure to UV light. Moreover sclerotia production was observed in only 3 of 5 toxigenic isolates. Furthermore one isolate from a sinus specimen was identified as Aspergillus oryzae. This is believed to be the first report of sinusitis due to A. oryzae from Iran. Conclusion: Some of clinical A. flavus isolates could have aflatoxin and sclerotia producing ability, but not necessarily all aflatoxigenic A. flavus isolates are capable of producing sclerotia.